Customer engagement and co-created value in social media. Issue 6 (3rd October 2019) - Quach, Sara; Shao, Wei; Ross, Mitchell; Thaichon, Park
Abstract : Purpose: The purpose of this paper is to understand the relationship between customer participation, co-created value and customer engagement as well as customer motivation involved in this process. Design/methodology/approach: Respondents were randomly exposed to one of the six types of social media scenarios. A total of 181 respondents were drawn from an MTurk opt-in survey panel of individuals who resided in America and were over the age of 18 years. Findings: Overall, the results of this study showed that as the level of customer participation increased, the level of co-created value decreased. The relationship between customer participation and customer engagement was fully mediated by co-created value. Extrinsic motivation was found to moderate the relationship between customer participation and co-created value but did not moderate the relationship between customer participation and customer engagement. Moreover, customer engagement was at its highest when an external reward was not offered, in other words, when customers were intrinsically motivated. Furthermore, when an external reward was offered, a significant effect of privacy concern on customer engagement was observed. Originality/value: The study extends the current understanding of customer engagement through value co-creation, customer participation and perceptions of privacy in firm-initiated activities in social media.